Alternatives to the constitution of Cádiz in New Spain: republicanism and the insurgent constitutional decree of Apatzingán (1814). Issue 3 (1st September 2016) - Andrews, Catherine
Abstract: This article compares the Decreto Constitucional para la libertad de la América Mexicana, published in Apatzingán by the insurgents of New Spain in 1814, with the 1812 Constitution of Cádiz which established a constitutional monarchy in the Spanish Empire. It argues that the Decreto Constitucional cannot be understood as simply a product of Hispanic political thought and a reflection of the Cádiz text. Rather, it contends that the decree published in Apatzingán represents an alternative republican response to the dissolution of the Spanish monarchy. This alternate constitutional settlement drew on the debate of constitutional ideas that had taken place in New Spain since 1808 and was grounded in many of the same ideas as those present in the Pennsylvanian Constitution of 1776 and the first French republican constitutions of 1793 and 1795.